Status of mangrove ecosystems in the waters of Senggarang Besar, Tanjungpinang City, Riau Islands Province - Muzadid Salam; Febrianti Lestari; Susiana Susiana (Sekolah Tinggi Ilmu Pertanian Wuna, 2023)
The waters of Senggarang Besar are located in Senggarang Village, Tanjungpinang Kota District. The waters of Senggarang Besar have a fairly large mangrove ecosystem plus many mangrove seedling planting activities in the coastal waters of Senggarang Besar. Mangrove ecosystems have a variety of natural resources that are abundant and diverse. Mangroves are the most potential ecosystems because mangroves support the diversity of flora and fauna in aquatic communities and play a significant role in human survival based on economic, community and environmental perspectives. This study aims to determine the density, canopy cover, and status of mangrove ecosystems in the waters of Senggarang Besar. This research was conducted in September-December 2022 located in the waters of Senggarang Besar Tanjungpinang City, Riau Islands Province. Determination of observation stations using direct survey method in the field with 3 station points with 6 plots at each station, based on the presence of mangrove ecosystems. Determination of the retrieval point using purposive sampling method. Mangarove ecosystem species found in the waters of Senggarang Besar Tanjungpinang City Riau Islands Province there are 4 species including: Rhizophora apiculata, Bruguiera gymnorhiza, Xylocarpus granatum, and Avicenia marina. With density and cover values at station 1, 3900 ind/ha and 81.00%, at station 2, 1433.33 ind/ha and 69.98%, and station 3, 1446.7 ind/ha and 69.08%. The level of damage to the mangrove ecosystem in the waters of Senggarang Besar Tanjungpinang City, Riau Islands Province at station 1 includes good, very dense criteria based on KepMen LH No. 201 of 2004. While at stations 2 and 3 the level of damage includes good, moderate criteria based on KepMen LH No. 201 Year 2004.